Energy Efficiency Evaluation of Distribution Network Considering Power Quality Conditions. Issue 1 (August 2020) - Jiang, Limin; Huang, Wei; Sun, Beibei; Meng, Junxia
Abstract: There are three-phase imbalance, voltage deviation, frequency fluctuation and other power quality problems in the traditional AC distribution network, which are difficult to meet the demand of power users for high power quality. The AC-DC hybrid distribution network is superior to the AC distribution system in terms of reducing power loss and improving power supply quality. Based on the research status of energy-saving indexes of distribution network, considering the characteristics of AC-DC hybrid distribution network, this paper analyzes the factors that affect the energy efficiency level of AC-DC hybrid distribution system, constructs the evaluation index system, determines the classification evaluation standards of different indexes according to the relevant standards, and puts forward the quantitative evaluation method of the energy efficiency level of AC-DC hybrid distribution network.